1990
DOI: 10.1007/bf01706357
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of measurements of blood pressure, heart-rate and oxygenation during inter-hospital transport of the critically ill

Abstract: Critically ill patients transferred between hospitals are often inadequately monitored in transit, with outcome adversely affected. In 22 such patients, we compared direct and palpated measurements of systolic pressure, oscilloscopic and aneroid manometric measurements of mean pressure, ECG and palpated measurements of heart-rate and clinical and oximetric assessments of oxygenation. On average palpated readings of systolic pressure under-read direct readings by 29% and palpated readings of heart-rate under-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the test was extended to 30 seconds and if necessary a stethoscope was placed over heart when pulse was difficult to count. In HUNT 3, RHR was assessed by echocardiography recordings, and one can expect lower heart rates using this procedure; however, previous studies [33], [34] have shown that RHR assessment by palpation or by auscultation have strong correlation with electrocardiographic measurements, and could be an adequate surrogate measure in the absence of electrocardiography. The temporal decrease in RHR in present study is consistent with other longitudinal studies [11], [35] that have shown a considerable decline in RHR over the years, independent of age and presence of other cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the test was extended to 30 seconds and if necessary a stethoscope was placed over heart when pulse was difficult to count. In HUNT 3, RHR was assessed by echocardiography recordings, and one can expect lower heart rates using this procedure; however, previous studies [33], [34] have shown that RHR assessment by palpation or by auscultation have strong correlation with electrocardiographic measurements, and could be an adequate surrogate measure in the absence of electrocardiography. The temporal decrease in RHR in present study is consistent with other longitudinal studies [11], [35] that have shown a considerable decline in RHR over the years, independent of age and presence of other cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that pulse measurements by palpation or by auscultation are both strongly correlated with electrocardiographic findings, and may be adequate surrogate measures for RHR in the absence of electrocardiography. 21,22 Although measurement error is a common weakness, it is not likely to be systematically related to the risk of subsequent IHD, and therefore, a potential measurement error is expected to lead to an underestimation of the true association and not to create a spurious overestimate.…”
Section: Commentmentioning
confidence: 99%
“…Blood pressure by palpation provides only an estimate of systolic pressure. 5 Without an auscultated diastolic pressure, the pulse pressure (difference between systolic and diastolic pressure) cannot be calculated. Because a decrease in the pulse pressure may provide an early clue to the presence of hypovolemic shock, the fi eld provider measuring only palpated systolic blood pressure may miss this important clue.…”
Section: Discussionmentioning
confidence: 99%